Study of Gasohol as Alternative Fuel for Gasoline Substitution: Characteristics and Performances - Bardi Murachman; Dicky Pranantyo; Eddie Sandjaya Putra (Center of Biomass & Renewable Energy (CBIORE), 2014)
Gasohol is a mixture of premium petrol (gasoline) with alcohol, in this case ethanol. The use of gasohol can reduce fuel consumption without having to modify the existing engine. Therefore, this research is conducted to study the characteristics and performance of gasohol in various mixing ratios, which includes analysis of physical properties and the use of gasohol in the machine. Results show that the addition of technical ethanol at 7.0169%v increases the value of gasohol vapor pressure on the value of 8.6682 psi (7.7 psi for regular gasoline). Gasohol with technical ethanol content above 30%v decreases vapor pressure, promotes phase separation, and causes a sharp drop in temperature from 40%v distillation. In term of corrosivity, gasohol with up to 50%v ethanol content has the same corrosion level with regular gasoline, which is corrosion level 1A. Based on gasohol characteristics test, it is known that gasohol with technical ethanol content below 20%v can be used as a fuel substitute for gasoline. Real-time performance test of gasohol in engines has shown that the addition of ethanol content in gasohol tend to increase the engine power at a certain compression ratio, but it also increases fuel consumption because the heat value of ethanol is lower than gasoline. Machine in gasohol with ethanol content below 20%v can operate smoothly without having to modify the engine. Based on the studies that have been done, gasohol in the range of 10%v ethanol content is well-functioned as a substitute for gasoline fuel and meets fuel specifications required by the General Director of Oil and Gas. The feasibility of using gasohol as an alternative fuel can be studied further.